2000
DOI: 10.1523/jneurosci.20-22-08614.2000
|View full text |Cite
|
Sign up to set email alerts
|

Key Role for the Epsilon Isoform of Protein Kinase C in Painful Alcoholic Neuropathy in the Rat

Abstract: Chronic alcohol consumption produces a painful peripheral neuropathy for which there is no reliably successful therapy, attributable to, in great part, a lack of understanding of the underlying mechanisms. We tested the hypothesis that neuropathic pain associated with chronic alcohol consumption is a result of abnormal peripheral nociceptor function. In rats maintained on a diet to simulate chronic alcohol consumption in humans, mechanical hyperalgesia was present by the fourth week and maximal at 10 weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
124
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(144 citation statements)
references
References 55 publications
(54 reference statements)
13
124
1
3
Order By: Relevance
“…A significant increase was also observed in thalamus for both isoforms and in striatum only for PKCc. Both c and e isoforms of PKC have been previously shown to be implicated in hyperalgesia [1,7]. A number of studies over the last several years indicate that brainstem descending pathways linking the PAG, the rostral ventromedial medulla (RVM) and the spinal cord constitute a major mechanism in the modulation of pain transmission [8].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase was also observed in thalamus for both isoforms and in striatum only for PKCc. Both c and e isoforms of PKC have been previously shown to be implicated in hyperalgesia [1,7]. A number of studies over the last several years indicate that brainstem descending pathways linking the PAG, the rostral ventromedial medulla (RVM) and the spinal cord constitute a major mechanism in the modulation of pain transmission [8].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the underlying intracellular signaling pathways, as well as the mechanoreceptors involved, remains fragmentary. Nevertheless, one signaling component, the ⑀ isoform of protein kinase C (PKC⑀), has turned out to be important in nociceptor sensitization caused by inflammation (Khasar et al, 1999b;Numazaki et al, 2002;Sweitzer et al, 2004), peripheral neuropathies such as diabetes , chronic alcoholism (Dina et al, 2000), and cancer chemotherapy (Dina et al, 2001;Joseph and Levine, 2003b), as well as the transition from acute to chronic pain (Aley et al, 2000;Parada et al, 2003a,b). However, a signaling pathway leading to activation of PKC⑀ remains still to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that the Ca 2ϩ -mediated cell signaling pathways are crucial to nociception (e.g., Saegusa et al, 2001;Kim et al, 2003). In particular, Ca 2ϩ activates protein kinase C, specific isoforms of which have been demonstrated to be important in studies employing various experimental neuropathic pain models (Malmberg et al, 1997;Hua et al, 1999;Dina et al, 2000).…”
mentioning
confidence: 99%